Giant Frontoethmoidal osteoma with orbital involvement - Pankaj Gupta; Arvind Sharma; Jitendra Singh; Tarun Ojha (Romanian Neurosurgery, 2017)
Osteomas are benign tumours that involve paranasal sinuses more than other parts of body. Frontal sinus is most common while sphenoid is least one. They are usually asymptomatic and diagnosed incidentally on imaging for other reasons. Giant variety of frontoethmoid osteoma is very rare and only few cases are described in literature. Orbital involvement in giant frontoethmoid osteoma is even rarer. Due to threat to vision, this variety is an indication for surgical intervention followed by reconstruction of defect. As these tumours are very large, endoscopic approaches are less indicated and there is no clear consensus which open surgical approach is better. We are reporting such a rare case of giant frontoethmoid osteoma causing proptosis and restriction of eye movement that was treated with open surgical approach.